Measuring the equity impacts of government subsidies for electric vehicles - Caulfield, Brian; Stefaniec, Agnieszka (My University, 2022)
A shift to electric vehicles (EV) is seen as one of the main methods to decarbonise the transportation sector. However, issues have also been raised regarding charging infrastructure, EV reliability and range, as well as the battery environmental and social credentials. Notwithstanding governments, intergov- ernmental organisations, and research entities have ploughed ahead to promote this transition, but the challenge is the uptake and public acceptance. Grants and financial subsidies have been developed to facilitate this shift. Our study investigates the characteristics of the private EV household charger pop- ulation using a regression model and spatial analysis to determine the influences of income, car ownership and economic status on EV take up rates. Data on the installation of EV household chargers are used in this paper as a proxy for EV ownership, due to data limitations. The results indicate that 1) urban areas are more likely to see higher concentrations of EV ownership, 2) an income and equity gap exists between those that have adapted electric mobility. This finding is very important because it suggests that lower income categories may have a financial barrier to shifting to EVs.
PUBLISHED
Keywords: Electric vehicles; Charging points; Household income; Social acceptance; Spatial analysis; Smart & Sustainable Planet; Environmental Impacts of Transport; Transport